2012
DOI: 10.2147/opth.s34848
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of repeated 5-fluorouracil needling for failing and failed filtering surgeries based on simple gonioscopic examination

Abstract: PurposeTo evaluate the success rate of a modified bleb needling technique in eyes with previous glaucoma surgery that had elevated intraocular pressure.MethodsA retrospective study of 24 eyes of 24 patients that underwent repeated bleb needling performed for failing and failed blebs on slit lamp with 5-fluorouracil (5-FU) injections on demand. This was performed after gonioscopic examination to define levels of filtration block.ResultsThere was significant reduction of mean IOP from 36.91 mmHg to 14.73 mmHg at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It is frequently used in ophthalmology as an adjuvant in the treatment of various ocular diseases such as pterygium [2] and glaucoma [3] to improve the success of clinical therapy. In glaucoma surgery, 5-FU was introduced as an adjunct agent administered by repeated subconjunctival injections after trabeculectomy to inhibit the proliferation of fibroblasts [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is frequently used in ophthalmology as an adjuvant in the treatment of various ocular diseases such as pterygium [2] and glaucoma [3] to improve the success of clinical therapy. In glaucoma surgery, 5-FU was introduced as an adjunct agent administered by repeated subconjunctival injections after trabeculectomy to inhibit the proliferation of fibroblasts [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies present similar successful results (8,9). Tatham et al (8) reported that 5-FU is an effective technique for trabeculectomy bleb remodeling and can result in a sustained reduction in IOP.…”
Section: Discussionmentioning
confidence: 68%
“…Tatham et al (8) reported that 5-FU is an effective technique for trabeculectomy bleb remodeling and can result in a sustained reduction in IOP. Rashad (9) reported that a significant reduction of mean IOP from 36.91 mmHg to 14.73 mmHg is achieved at the final follow-up and the overall success rate was 92%. He added that repeated needling with adjunctive 5-FU proved a highly effective in managing bleb failure (9).…”
Section: Discussionmentioning
confidence: 99%
“…IOP > 30 mmHg before the procedure, high IOP after the procedure, lack of use antimetabolite in previous filtration surgery, type of glaucoma are the risk factors that affect the efficiency of the BNR procedure [22]. Generally, repeated BNR with adjunctive 5-FU provide revive of filtration in dysfunctional bleb and prevent other surgery [23]. Indeed, additional surgery may be needed in some cases.…”
Section: Discussionmentioning
confidence: 99%